Struktur Komunitas Fitoplankton sebagai Indikator Kualitas Air di Kali Mas Kota Surabaya - Kabul Fadilah; Muhammad Abdus Salam Jawwad; Syadzadhiya Qothrunada Zakiyayasin Nisa’ (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Phytoplankton is an aquatic organism that is sensitive to environmental changes. Kali Mas is one of the rivers that passes through the city of Surabaya, and is a source of water needs for various domestic and industrial needs. The purpose of this study was to determine the status of Kali Mas water quality based on the phytoplankton community structure, which includes: diversity, abundance, evenness, dominance, and saprobic index. The method used in this study is purposive sampling. Water and phytoplankton samples were taken from 5 stations along the Kali Mas flow. The identification results of the phytoplankton found consisted of 10 classes, which consisted of: Bacillariophyceae (44.19%); Chlorophyceae (6.33%); Chrysophyceae (0.26%); Cyanophyceae (24.9%); Conjugatophyceae (7.49%); Dinophyceae (2.84%); Fragilariophyceae (1.29%); Trebouxiophyceae (8.14%); Ulvophyceae (3.18%); and ‎Xanthophyceae (0.65%). Diversity index ranged from 2.35-2.96; evenness index 0.72-0.87; and the dominance index is in the range of 0.05-0.148. Meanwhile, based on the saprobic index, Kali Mas is at 1.05. This value indicates the condition of Kali Mas waters is in β - Meso/oligosaprobic conditions with a mild level of pollution.